Hubungan Perilaku Makan Dengan Kejadian Kurang Energi Kronik (KEK) Pada Remaja Putri - Sukmawati Sukmawati; Mustamin Mustamin; Adriyani Adam; Ana Purnama Ningsih (Direktorat Politeknik Kesehatan Makassar, 2024)
Chronic lack of energy is one of the main nutritional problems experienced by many teenagers, especially young women. Based on the results of Riskesdas data (2018), the prevalence of KEK among adolescent girls in Indonesia is 36.3%. Adolescents who experience CED are at risk of giving birth to premature babies, bleeding during delivery, infant and child deaths and giving birth to babies <2.5 kg which is often called Low Birth Weight (LBW). The aim of the research is to determine the relationship between eating behavior and the incidence of chronic energy deficiency in adolescent girls. The type of research used is analytical research with a cross-sectional study approach. The research was carried out from June to August 2023. The sample in this research was all class XI female students at SMA Negeri 21 Makassar who were selected as samples with a total of 75 people. The variables in this research are the level of knowledge, attitudes and actions regarding balanced nutrition obtained using a questionnaire. The statistical analysis used was the chi square test. The statistical test results of the relationship between the level of knowledge and action and KEK both show a value of p=0.00 (p<0.05), meaning that there is a significant relationship between knowledge and action and the incidence of KEK. The relationship between attitude and SEZ shows a value of p=0.07 (p>0.05), meaning that there is no significant relationship between attitude and the incidence of SEZ. It was concluded that young women in the context of this research had good knowledge and actions towards balanced nutrition, even though their attitudes were predominantly negative. It is hoped that teenagers will further increase their knowledge which will later be able to change their attitudes regarding balanced nutrition through persuasion and pressure from those around them so that they are aware of the importance of health by meeting nutritional needs with balanced nutrition. Keywords : KEK, Knowledge, Attitude, Action